2017
DOI: 10.1038/onc.2017.247
|View full text |Cite
|
Sign up to set email alerts
|

Elevated tumor LDLR expression accelerates LDL cholesterol-mediated breast cancer growth in mouse models of hyperlipidemia

Abstract: Obesity is associated with an increase in cancer-specific mortality in women with breast cancer. Elevated cholesterol, particularly low-density lipoprotein cholesterol (LDL-C) is frequently seen in obese women. Here, we aimed to determine the importance of elevated circulating LDL, and LDL receptor (LDLR) expression in tumor cells, on the growth of breast cancer using mouse models of hyperlipidemia. We describe two novel immunodeficient mouse models of hyperlipidemia (Rag1−/−/LDLR−/− and Rag1−/−/ApoE (apolipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
136
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(152 citation statements)
references
References 50 publications
6
136
0
1
Order By: Relevance
“…Consistent with this, our study revealed that GC cells did not proliferate in a glucose-free medium. However, there are several reports on the association between tumorigenesis and lipid uptake in various types of cancers [ 23 , 24 ]. Hypercholesterolaemia, which is a common metabolic disorder in obese people, has been shown to increase the risk of gastroenterological cancers, and substantial epidemiologic evidence links hypercholesterolaemia to an increased risk of colorectal cancer [ 25 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, our study revealed that GC cells did not proliferate in a glucose-free medium. However, there are several reports on the association between tumorigenesis and lipid uptake in various types of cancers [ 23 , 24 ]. Hypercholesterolaemia, which is a common metabolic disorder in obese people, has been shown to increase the risk of gastroenterological cancers, and substantial epidemiologic evidence links hypercholesterolaemia to an increased risk of colorectal cancer [ 25 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions, the inflammatory phenomenon is induced by adipose tissue and macrophage infiltration that favor the secretion of soluble factors, such as adipokines and extracellular vesicles. In line with this notion, it has been shown that overexpression of LDLR or tumor cells treatment with LDL are associated with an increase in growth and proliferation of mammary cancer cells in vitro and in vivo models …”
Section: Discussionmentioning
confidence: 71%
“…Cells obtain cholesterol from the LDLRs present on the cell surface [109]. High expression of LDLR has been associated with tumours from breast cancer cells in mouse models with hyperlipidemia [110]. Furthermore, knockdown of LDLR was found to reduce tumour growth in these mouse models.…”
Section: Hsa-mir-128 and Hsa-mir-223 Potentially Regulate Genes Involmentioning
confidence: 99%